An Improvement Proposal to the Static Friction Model. (12th June 2013) - Sánchez-Mazuca, Sergio; Campa, Ricardo
Abstract : Friction is a force acting against the relative motion between two surfaces in contact. This phenomenon is present in all mechanical systems and has a great impact on the control area. The design of mechatronic systems and the compensation techniques require a broad knowledge of the effects that friction produces. The phenomenon has two well-defined phases: static friction presents before the motion between the surfaces in contact is clearly visible, while kinetic friction appears when that motion at large scale has already started. There are different friction models for each of those phases. In this work we propose an improvement to the static friction models, which consist in assuming that the maximum static friction coefficient is no more a constant but a function of the rate of change of the external force that produces the motion. After explaining and justifying the proposal, the procedure for obtaining the parameters of the new model is mentioned. At the end, an experimental study on a direct-drive motor allows us to validate the proposed model.